Incivility and Sexual Harassment at the Workplace: Occupational Health Impact - Liliana Díaz G; Bernardo Moreno J; Eva Garrosa H; Julia Sebastián H (Universidad de Antioquia, 2011)
In recent years, interest and research on workplace aggression have increased, since it is a serious occupational health problem with negative consequences for both employees and organizations. Objective: to analyze the relationships between different forms of workplace aggression (incivility and sexual harassment), counterproductive work behaviors, and job satisfaction. Methodology: a cross-sectional study, involving 460 employees from the services sector of Madrid, Spain. Self-report questionnaires were used to assess the employees' potential exposure to workplace aggression, as well as their level of job satisfaction, and the manifestation of negative behaviors towards the organization. Results: a significant negative association was found between the studied forms of workplace aggression and job satisfaction. Likewise, a significant positive association between the forms of workplace aggression and counterproductive work behaviors was also found. Conclusions: workplace aggression may have negative consequences for a company. It can affect employee satisfaction and encourage counterproductive behaviors. Therefore, it is important, within the field of occupational health, to implement programs that prevent workplace aggression as well as clear intervention protocols to address it whenever it occurs.